Enhancing peripheral nerve regeneration: A novel nanofibrous nerve conduit with bioactive poly(ɛ-caprolactone), collagen, and retinoic acid nanofiber - Muhammad Aseer; Niloofar Nazeri; Nasrollah Tabatabaei; Zohreh Arabpour; Reza Faridi Majidi; Hossein Ghanbari (Nanomedicine Journal)
Objective(s): Peripheral nerve injury (PNI) is a critical clinical issue primarily caused by trauma. Tissue engineering approaches using nanofiber scaffolds have been extensively explored to improve material quality and create an environment resembling the natural extracellular matrix (ECM). Materials and Methods: In this study, we employed electrospinning technique to fabricate a composite scaffold comprising poly(ɛ-caprolactone) (PCL) and collagen (Col) loaded with all-trans retinoic acid (RA), a neural patterning and signaling chemical known to promote nerve regeneration. Results: The synthesized nanofiber scaffold exhibited a diameter of 391±79 nm and a tensile strength of 250±13 MPa, providing sufficient support for native peripheral nerve regeneration. The inclusion of Col enhanced the scaffold’s hydrophilic behavior (contact angle: 43±6°), ensuring stability in an aqueous solution. Moreover, the results demonstrated the proliferation and adhesion of nerve cells on the scaffold, aligning with the directions of the warp and weft of the nanofiber mat. Importantly, the scaffolds demonstrated non-toxicity, making them a promising substitute for the native ECM for enhanced cell attachment and proliferation. Finally, immune-histochemistry analyses further confirmed that the scaffolds supported the release and growth of neurites, promoting cell differentiation toward nerve repair. Conclusion: The RA-loaded scaffolds demonstrated the enhanced biocompatibility, supported neurite growth, and showed potential as a capable candidate for nerve regeneration.